Liminal politics in the new age of disease
1 online resource.
Keywords: Liminal Politics in the New Age of Disease explores the phenomenon of liminal politics': an open-ended state of exception' in which normal rules no longer apply, and things which were previously unimaginable become possible - even appearing remarkably quickly to represent a new normal'. With attention to the emergency measures introduced to counter the spread of Covid-19, it shows how the emergency suspension of democratic accountability, ordinary life and civil liberties, while accidental, can lend itself to orchestration and exploitation for the purpose of political gain by trickster' or parasitic' figures. An examination of the cloning of political responses from jurisdiction to jurisdiction, with little consideration of their rational justification or local context, this volume interrogates the underlying dynamics of a global technological mimetism, as novel technocratic interventions are repeated and the way is opened for new technologies to reorganise social life in a manner that threatens the disintegration of its existing patterns. As such, it will appeal to scholars and students of sociology, social theory and anthropological theory with interests in political expediency and the transformation of social life.